Structural characteristics of light-frame wood shear walls with various construction detailing. (15th February 2020) - Bagheri, M.M.; Doudak, G.
Highlights: The design code under-estimates the deflection of the wall significantly. Bending deflection does not follow the cantilever assumptions. No panel shear deformation was observed during the test. The deflection was affected by the overall number of studs, not solely by the end studs. Nail size and spacing had the highest impact on the wall behavior. Abstract: A total of 26 full-scale walls were investigated with the aim to study the effects of construction details variation on the behavior of the shear walls. The deflected shape of the end studs was found to be non-linear with regard to loading level. The bending component seems affected by the rotation of the sheathing panels and nail slip. No significant panel shear deformation was observed. The deflection expression in the wood design standard was found to under-estimate the nail slip component. Hold-down system used in this study behaved in a non-linear manner with higher initial stiffness than that assumed in design. The strength and stiffness correlated almost directly to the inverse of the wall aspect ratios, with no clear trends found on ductility. Walls with aspect ratios not permitted according to the wood design standard followed similar strength and stiffness trends and had sufficient ductility ratios as those with lower aspect ratios. Adding more end studs and changing the size of the studs had no significant effect on the overall wall capacity and little effect on its stiffness. The wall strength was significantly affected by the nail diameter and nail spacing, but this effect was not linear. The study also showed that having continuous hold-down connections has a positive effect on the capacity, stiffness and ductility of the wall. Having no hold-down adversely affected the wall capacity and stiffness. A shear wall model was developed and the results from the model were compared with those obtained experimentally. It was found that the model was capable of predicting the wall behaviour with reasonable accuracy.